The plasma concentration of the B cell activating factor is increased in children with acute malaria - Nduati, E; Gwela, A; Karanja, H; Mugyenyi, C; Langhorne, J; Marsh, K; Urban, B (2011)
Malaria-specific antibody responses in children often appear to be short-lived but the mechanisms underlying this phenomenon are not well understood. In this study, we investigated the relationship between the B-cell activating factor (BAFF) and its receptors expressed on B cells with antibody responses during and after acute malaria in children. Our results demonstrate that BAFF plasma levels increased during acute malarial disease and reflected disease severity. The expression profiles for BAFF receptors on B cells agreed with rapid activation and differentiation of a proportion of B cells to plasma cells. However, BAFF receptor (BAFF-R) expression was reduced on all peripheral blood B cells during acute infection, but those children with the highest level of BAFF-R expression on B cells maintained schizont-specific immunoglobin G (IgG) over a period of 4 months, indicating that dysregulation of BAFF-R expression on B cells may contribute to short-lived antibody responses to malarial antigens in children. In summary, this study suggests a potential role for BAFF during malaria disease, both as a marker for disease severity and in shaping the differentiation pattern of antigen-specific B cells. © The Author 2011. Published by Oxford University Press on behalf of the Infectious Diseases Society of America. All rights reserved.